Is Consumptive Behavior Effected by Lifestyle and Conformity? Study at Fashion Community in Sukabumi - M. Khoirul Fahmi Dwi Nova; Erna Susilawati (Journal of Economics, Management, Business and Accounting (JEMBA), 2022)
The growth of e-commerce in Indonesia in recent years has experienced very rapid growth. One of the items most often purchased by Indonesian people in e-commerce is fashion. This is caused by various things, one of them is the lifestyle of the community itself and conformity, this shopping behavior over time can lead to consumptive behavior, including the fashion community in Sukabumi. This study aims to determine the relationship and influence of Lifestyle and Conformity on Consumptive Behavior in the Community, either partially or simultaneously. The research that will be conducted is quantitative research with descriptive and verification research methods. Total population in this study 220 people, and this study uses the Slovin formula to determine the sample size with a margin of error of 10%, and the result is 69 people for the sample. The results of the study partially have a positive and significant influence on the Lifestyle variable on Consumptive Behavior. Partially there is a positive and significant influence of the Conformity variable on Consumptive Behavior and simultaneously there is a positive and significant influence of the Lifestyle and Conformity variable on Consumptive Behavior